Contemporary forms of international movement of capital - Šovran, Sanja; Hadžić, Miroljub (The European Journal of Applied Economics, 2016)
International movement of capital is one of the most important forms of international economic cooperation and achievement of strategic goals of enterprises. It leads to international diversification of business activities, strengthening of competitive advantage, changes in economic structures, employment rates and economic stability of participating countries. The present research addresses the contemporary forms of international movement of capital, with an emphasis on the public-private partnerships and concessions. The creation of different forms of public-private partnerships (PPPs) in Serbia gained in importance in the early ‘90s of the 20th century. PPP implies joint activities within the framework of which the public and private sector pool resources, especially financial capital and expertise in order to meet the public needs of local, regional or national significance for adequate resource allocation. This type of partnership between the public and private sector has become an effective way towards a more rational use of limited resources and development of business entities from different sectors. The partnership of the public and private sector is particularly important in the construction and maintenance of transportation and other infrastructure facilities. Concessions represent a special form of public-private partnerships.